2004
DOI: 10.1186/1471-2407-4-37
|View full text |Cite
|
Sign up to set email alerts
|

Atypical glandular cells in conventional cervical smears: Incidence and follow-up

Abstract: BackgroundAtypical glandular cells on cervical smears are often associated with clinically significant uterine lesions. The frequency and accuracy of AGC-NOS (i.e. atypical glandular cells, not otherwise specified) diagnoses, regardless of the gland cell type or the degree of suspicion, and their outcome were investigated.MethodsFrom January 1, 1990 to December 31, 1999 a total of 261 patients had an AGC-NOS diagnosis made by conventional cervical Papanicolaou smear interpretation representing 0.05% of all Pap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
34
1
8

Year Published

2005
2005
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(52 citation statements)
references
References 36 publications
7
34
1
8
Order By: Relevance
“…There has Address correspondence and reprint requests to Rita Demopoulos, 24 Sycamore Road, Scarsdale, New York 10583. E-mail: rita.demopoulos@ med.nyu.edu (4)(5)(6)(7)(8)(9)(10). However, we found no studies in the literature that focused on the truly negative Pap smears in patients with invasive endocervical adenocarcinoma, which correlated the Pap smears with the pathology findings for a possible explanation.…”
mentioning
confidence: 73%
“…There has Address correspondence and reprint requests to Rita Demopoulos, 24 Sycamore Road, Scarsdale, New York 10583. E-mail: rita.demopoulos@ med.nyu.edu (4)(5)(6)(7)(8)(9)(10). However, we found no studies in the literature that focused on the truly negative Pap smears in patients with invasive endocervical adenocarcinoma, which correlated the Pap smears with the pathology findings for a possible explanation.…”
mentioning
confidence: 73%
“…3 a, b). Similarly, another case was reported as invasive SCC on cytology, which showed [8] 21,854 83 0.4 Gutman et al [9] 11,800 45 0.38 Crasta et al [10] 10,787 19 0.17 Adhya et al [11] 18,376 65 0.35 Ajit et al [12] 22,618 74 0.32 Jeng et al [13] 51,419 49 0.09 Scheiden et al [14] 522 adenosquamous carcinoma on histopathology. This was due to the presence of only malignant squamous cells on cytology ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…9 René Scheiden et al had 56% of the patients with significant cancerous and precancerous conditions emphasising the requirement of complete and careful evaluation. 10 Our study revealed 9cases (64.3%) with significant precancerous (1case) and cancerous lesions (8 cases) on histopathology follow up, out of 14 atypical endometrial cells in cytology. Increased rate of detection of precancerous and cancerous lesion was because we included only symptomatic patients as study group.…”
Section: Discussionmentioning
confidence: 51%